Phylogeography of an Atlantic forest passerine reveals demographic stability through the last glacial maximum - Batalha-Filho, Henrique (2012)
In this study we analyzed the phylogeographic pattern and historical demography of an endemic Atlantic forest (AF) bird, Basileuterus leucoblepharus, and test the influence of the last glacial maximum (LGM) on its population effective size using coalescent simulations. We address two main questions: (i) Does B. leucoblepharus present population genetic structure congruent with the patterns observed for other AF organisms? (ii) How did the LGM affect the effective population size of B. leucoblepharus? We sequenced 914. bp of the mitochondrial gene cytochrome b and 512. bp of the nuclear intron 5 of beta-fibrinogen of 62 individuals from 15 localities along the AF. Both molecular markers revealed no genetic structure in B. leucoblepharus. Neutrality tests based on both loci showed significant demographic expansion. The extended Bayesian skyline plot showed that the species seems to have experienced demographic expansion starting around 300,000. years ago, during the late Pleistocene. This date does not coincide with the LGM and the dynamics of population size showed stability during the LGM. To further test the effect of the LGM on this species, we simulated seven demographic scenarios to explore whether populations suffered specific bottlenecks. The scenarios most congruent with our data were population stability during the LGM with bottlenecks older than this period. This is the first example of an AF organism that does not show phylogeographic breaks caused by vicariant events associated to climate change and geotectonic activities in the Quaternary. Differential ecological, environmental tolerances and habitat requirements are possibly influencing the different evolutionary histories of these organisms. Our results show that the history of organism diversification in this megadiverse Neotropical forest is complex.